2012
DOI: 10.1210/jc.2012-2484
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Functional Estrogen Receptor in Parathyroid Adenomas

Abstract: Parathyroid tumors express ERβ1 and ERβ2. Transcriptional changes after ERβ1 activation and correlation to clinical features point to a role of estrogen signaling in parathyroid function and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 216 publications
(210 reference statements)
4
26
0
1
Order By: Relevance
“…inhibitory feedback by the vitamin D receptor (VDR) and fibroblast growth factor 23 (FGF23)/Klotho-axes (14, 15, 16). Additional effects mediated by estrogens and progesterone have been described previously (17, 18). …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…inhibitory feedback by the vitamin D receptor (VDR) and fibroblast growth factor 23 (FGF23)/Klotho-axes (14, 15, 16). Additional effects mediated by estrogens and progesterone have been described previously (17, 18). …”
Section: Introductionsupporting
confidence: 59%
“…The rationale behind these discrepancies may be due to differences in the study populations, including the degree of vitamin D insufficiency. Specifically, the impact of vitamin D insufficiency may be limited in primary hyperparathyroidism diagnosed at an early stage (18, 19, 20, 21, 32, 40, 41). Indeed, our semi-quantitative immunohistochemistry may be too crude to accurately quantify the tumor PTH levels for weaker statistical relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, sporadic primary HPT can present at any age, with an increased incidence in postmenopausal women 4 7 30 42 52 53. A wide spectrum of clinical manifestations can be encountered, depending on the duration and degree of PTH oversecretion and resultant hypercalcaemia (tables 1 and 2).…”
Section: Clinical and Biochemical Featuresmentioning
confidence: 99%
“…Interestingly, further analysis of ERβ variants revealed that ERβ1 nuclear staining in the tumors was weaker compared to in the normal parathyroid rim (p = 0.026), and this difference was more evident in atypical adenomas (p = 0.045) and larger tumors (p = 0.029) [47]. The results from this study were repeated in a larger number of parathyroid tumors (n = 172) and 10 normal parathyroid glands [48].…”
Section: Expression Of Female Sex Steroids In Sporadic Parathyroid Tumentioning
confidence: 60%
“…By contrast, Wong et al [46] demonstrated ERα and ERβ expression in 100% of tissue samples from patients with primary and secondary hyperparathyroidism, although in some cases of secondary hyperparathyroidism the expression was weak. The expression of ERα and two other variants of ERβ, namely ERβ1 and ERβ2, were also studied by Haglund et al [47] in 37 sporadic parathyroid adenomas at both the mRNA and protein levels. In this study, parathyroid adenomas expressed low levels of the ERα gene, but relatively high levels of the ERβ gene.…”
Section: Expression Of Female Sex Steroids In Sporadic Parathyroid Tumentioning
confidence: 99%